2011
DOI: 10.1089/ars.2010.3646
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Schizophrenia: Pathogenetic and Therapeutic Implications

Abstract: Over a century, a wide-ranging variety of pathophysiological models and causal hypotheses have been conceptualized for schizophrenia. One among these is the role for free radical-mediated pathology in schizophrenia, indicating impaired antioxidant defense system (AODS) and presence of oxidative stress in patients with schizophrenia. For the past two decades, the whole investigative domain of AODS and oxidative stress has broadened to include the wider AODS components, direct central nervous system assays of AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 32 publications
4
94
0
2
Order By: Relevance
“…Since over a century that schizophrenia has been conceptualized there have been wide-ranging variety of pathophysiological models and causal hypotheses of schizophrenia [21]. One among these is the role for free radical-mediated pathology in schizophrenia that was proposed more than half century ago [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since over a century that schizophrenia has been conceptualized there have been wide-ranging variety of pathophysiological models and causal hypotheses of schizophrenia [21]. One among these is the role for free radical-mediated pathology in schizophrenia that was proposed more than half century ago [22].…”
Section: Discussionmentioning
confidence: 99%
“…Brain is particularly vulnerable to oxidative stress as a result of the relatively low levels of antioxidants, high levels of polyunsaturated fatty acids and increased need of oxygen [23,24]. In the intervening decades there has been a steady stream of evidence demonstrating the presence of oxidative stress in patients with schizophrenia [21]. In accordance with these implications, our results showed that TOS and OSI increased in our patient group compared to the controls, providing additional evidence of increased oxidative stress in schizophrenia (Tables 3 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of other antioxidants, including glutathione peroxidase (GSH-Px), also have been implicated (Abdalla et al, 1986;Stoklasová et al, 1986;Buckman et al, 1987;Altuntas et al, 2000). It has been suggested that low GSH-Px is a contributing factor to structural brain abnormalities (Buckman et al, 1990;Yao and Reddy, 2011). Several studies have reported that patients with bipolar disorder have significant alterations in antioxidant enzymes, lipid peroxidation, and nitric oxide levels (Andreazza et al, 2008), suggesting the role of free radicals and antioxidants in the pathophysiology of bipolar disorder Magalhães et al, 2011;Sarris et al, 2011).…”
Section: Oxidative Stress and Neuropsychiatric Disordersmentioning
confidence: 99%
“…Altered antioxidant defense and signs of oxidative insults are observed in patient samples (Yao et al, 2001). In this context, it has been shown that the activation of the ROS-producing NADPH oxidase NOX2 enzyme contributes to dysfunction of GABAergic interneurons after subchronic ketamine exposure in mice (Behrens et al, 2007(Behrens et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%